Incidence of Sport Injury in Contact and Non-Contact Sports - ÖZEN, ŞAHİN (MATTIOLI 1885, 2021)
The loads and impacts our bodies are exposed to during sportive activities may result in various sports injuries. In this context, the purpose of the present study was to define the prevalence, area and type of sport injuries of athletes and to determine the difference between the contact and non-contact sports depending on the certain variables like treatment methods and recovery times. The total of 185 athletes voluntarily participated in the present study. Sport branches of athletes were classified into two groups as contact (81) and non-contact (63) sports. The data were collected using sports injury questionnaire (SIQ) and socio-demographic attributes questionnaire via online Google Forms. Injury type percentages were as follows; 27,08% knee region, 14,58% shoulder and 12,49% ankle respectively. 66,67% of the athletes were reported being away from sports for longer than 4 weeks due to injuries. Following their injuries, 47,2% of athletes returned to sports after resting; 23,6% after surgical operations and 29,2% after rehabilitation treatments. No differences were found between contact and non-contact groups regarding treatment methods and recovery times. The data regarding injury histories and training exposure times could not be presented due to lack of information from sports clubs and trainers. We would like to suggest that health and athletic performance attributes of athletes should be evaluated on a regular basis using sport performance tests, an injury database should be created, and injury prevention measures should be taken into consideration.
Keywords: Sport injury; incidence; contact sports; non-contact sports; RISK-FACTORS; RUGBY UNION; FOOTBALL